Craniofacial morphometry in Saudi population - Siddika, Ayesha (2021)
The purpose of this research is to have a better understanding of the craniofacial morphometric structures and comparison of the sexual dimorphism of the Saudi population. The ethnicity, hard tissue,soft tissue and dental features should be considered during treatment, especially in orthodontics and orthognathic surgery. Lateral cephalometric radiograph for cephalometric analysis provides details about skeletal structure relationships, relationships between skeletal structures with the teeth and facial soft tissue structures. The lateral cephalometric radiographs help the orthodontists to pay attention to the current facial structures as well as predict future facial growth when planning a treatment plan for the patient. It is a cross sectional study of 500 lateral cephalometric radioghraphs which contain 250 males and 250 females. These samples were recruited from the Dental Center, King Khalid General Hospital, Hafer al Batin, Kingdom of Saudi Arabia with age group 18 to 30 years old. All the radiographs were traced by using CASSOS software. All the radiographs were analyzed by using Burstone, Down, Eastman, Holdaway, Jarabak, McNamara, Ricketts, Steiner, Tweed, Wits analysis. In this study there were some statistically differences in some of the measurements as compared to other established morphometric data, therefore Saudi population requires its own cephalometric analysis as a reference. Multi cephalometric analysis are essential for providing complete craniofacial morphometric information whereby it‘s included hard tissue, soft tissue and dental structures of its own racial group.